The informational logic of human rights : network imaginaries in the cybernetic age / Josh Bowsher. - Bowsher, Josh (Technicities., 2023)
What happens to the cultural politics of human rights when atrocities are rendered calculable, abuses are transformed into data, and victims become vectors? As human rights organizations have increasingly embraced information technologies this 'datafication' of rights has become both a reality and a pressing concern, one inextricably tangled up with questions regarding the broader political valences of human rights. Combining contemporary social and cultural theory with archival research and original ethnographic work, Josh Bowsher resituates recent critiques of human rights within ongoing theoretical discussions concerning informational capitalism, digital culture and the politics of data.